3D kinematic of three strides in classical cross-country skiing technique during world cup races (2009-2010) - Canclini, A.; Canclini, A.; Baroni, G.; Pozzo, R. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Classical style in cross-country skiing (XCS) was the unique technique used until 1984, and was divided in three principal strides: Diagonal stride (DS), double poling (DP) and DP with kick (DPk). Even though the motion actions remain the same for the most part, several changes were found since the 90s due to different causes (Lindinger 2007). New equipment and materials, better ski track preparation, increases in the training methodology, and the specific use of upper body segments emphasized in skating enhanced the velocity and the performance in all types of races. Moreover, in classical races the use of different "gears" (DS, DP, DPk) are distributed in different fractions and steepness of the course. The aim of this work was to collect and to analyze the 3D kinematics of the typical strides in classic XCS performed by elite skiers, both male and female, engaged in recent World Cup races.